Ranking the Level of Satisfaction about Online Ticket Booking - Ajith, V; Renugadevi, S (Journal of Advanced Research in Entrepreneurship, Innovation and SME Management, 2022)
Apart from consumer goods, sales and e-tailing, the online travelling sector has boomed in recent years and the number of users booking their tickets on the Web has been steadily growing. Decreasing number of people are now using the traditional paper ticket while almost all industries offer the possibility of online ticket reservation, commonly known as e-ticket. The online reservation system in India is undergoing a revolution. Almost all the transport sectors have invested in online reservation. This has given rise to the increased preference of customers, to whom requisite services are offered. Hence, it would be necessary to study and analyse the customer satisfaction level in online reservation. Therefore, this study was undertaken to explore satisfaction level of customers in in online reservation. Empirical method and convenient sampling technique was used for this study. Sample size was 100 and the period of study was 2015-16. Area ofstudy was Madurai, TN, India. The data was analysed by using Garret ranking. Primary and secondary sources were used for data collection. A questionnaire was developed and pre-tested for the study. How to cite this article: Renugadevi S, Ajith V. Ranking the Level of Satisfaction about Online Ticket Booking. J Adv Res Entrep Innov SMES Mgmt 2021; 4(2): 6-8.